Prognostic changes in lymphocyte subpopulations during the development of autoimmune complications in patients with DiGeorge syndrome - N. V. Davydova; N. V. Zinovieva; S. B. Zimin; O. V. Shvez; E. V. Galeeva; Yu. E. Konoplyannikova; O. V. Molochnikova; Yu. V. Petrova; G. N. Gildeeva; I. G. Kozlov (Медицинская иммунология, 2024)
Patients with 22q11.2 deletion syndrome (DiGeorge syndrome) are characterized by a combination of a wide range of pediatric problems with an immunodeficiency. Defects are characterized by T cell lymphopenia, changes in the functions and subpopulation composition of T and B lymphocytes. Disturbances in lymphocyte homeostasis can lead not only to severe infectious diseases, but also to autoimmune complications, especially in older children. The purpose of this study was to compare the subpopulations of T and B lymphocytes with and without autoimmune complications and to search for prognostic signs that precede the development of complications. The study included 20 patients aged 10 to 18 years with a confirmed diagnosis of DiGeorge syndrome. The patients were divided into 2 groups, according to the presence or absence of autoimmune complications. Subpopulations of lymphocytes were assessed by flow cytometry. No statistically significant differences were found between CD3 T lymphocytes, CD4 T helper, CD8 T cytotoxic and subpopulations of T helper (p > 0.05). However, in the group of patients with autoimmune complications, a statistically significant decrease in CD45RA+ naïve T helper cells was detected, both in relative (p = 0.020) and absolute number (p = 0.025) and regulatory T cells (respectively, p = 0.020 and p = 0.007). Among B-lymphocyte in patients with autoimmune complications, a decrease in memory B cells in relative (p = 0.031) and absolute number (p = 0.005) and switched memory (p = 0.016 and p = 0.031) was detected. But transitional B lymphocytes, on the contrary, were increased in relative quantity (p = 0.003). There were no differences between the groups in the level of plasmablasts, activated B-lymphocytes CD21lowCD38low, IgM only B-cells (p > 0.05). The ROC analysis showed that the most diagnostically and prognostically significant indicators are the relative number of CD45RA+ naive T cells (cut-off ≤ 28.7%), switched memory B cells – relative (cut-off ≤ 5.0%) and the absolute number (cut-off ≤ 11 cells/µL) and the relative number of transitional B cells (cut-off ≥ 12.9%). Our data confirm the important role of regular immunophenotyping and especially subpopulations of CD45RA+ naive T cells, switched memory B cells and transitional B cells in predicting autoimmune complications in this category of patients.